x-3y=8

-x+6y=-17

Thank you for the opportunity to help you with your question!

----------------------------------------------------------------------------------------

Adding the two equations, we get

x - 3y = 8

-x + 6y= -17

y = (-9)/3

y = -3

Substitute value of y in the first equation

x - 3*(-3) = 8

x + 9 = 8

x = 8 - 9

x = -1

So, solution is x = -1 , y = -3 .

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up